Akcja zabezpieczania bibliotek i zbiorów bibliotecznych w Śląskiej Bibliotece Publicznej w latach 1945–1947 (w świetle dokumentów z Archiwum Zakładowego) (PDF 17,13 MB) (Książnica Śląska, 2025)
The author, basing herself mainly on documents from the Archiveof the Silesian Library, described the participation of the Silesian Public Library during the securing libraries and library collections inthe Silesian Voivodeship in the years 1945–1947. She presented thelegal and organizational basis and participants of the action, as wellas its course and financing. The author described the effects of almosttwo years of activity in the field of searching, recovering, saving fromdestruction and dispersion valuable book collections that had beenmoved, leaved or abandoned in the Recovered Territories.